Diversidad de macroinvertebrados acuáticos indicadores de calidad 1 ¡ . de agua y su relación con los parámetros físicos y químicos en las lagunas "El Toro" y "Los Angeles" de la Provincia de Santiago de Chuco La Libertad, enero- agosto 2014. - Alcalde Risco, Sheila Karina (2015)
The objective of this investigation was to determine the diversity of aquatic_x000D_ macroinvertebrates (MIAs) such as water quality indicators and their relationship_x000D_ with physicochemical factors of the Province of Santiago De Chuco, La Libertad,_x000D_ January-August 2014, which information would serve to take action in the_x000D_ conservation and protection ofthese water bodies that are currently suffering many_x000D_ environmental impacts. In each lagoon we established five sampling stations in the edge ofthe water body, MIAs were collected using a Surber net, they were separated into plastic jars with 96% alcohol properly labeled, using taxonomic keywords were identified to the family level; the physicochemical factors also were evaluated in situ. Biological_x000D_ índices, J accard' s index, BMWP, · EPT were determined and finally the Pearson_x000D_ coefficient. A range of 19 and 10 families ofMIAs qualit)r indicators in the lagoon_x000D_ "El Toro" and "Los Ángeles" respectively were found, the most abundant family in_x000D_ both lagoons is Corixidae; according to the BMWP, the quality of water for the_x000D_ lagoon "El Toro" in the months of January, March and August was class III_x000D_ (polluted water) but July was Class N (very polluted water) and to the lagoon "El_x000D_ Toro" was similar. Concluding that in the lagoon "El Toro" is more diverse than the_x000D_ lagoon "Los Ángeles" Key words: aquatic macroinvertebrates, indicators of water quality,_x000D_ physicochemical factors, coefficient ofPearson.